2022
DOI: 10.1055/a-1826-0777
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Loading on Cementoblasts: A Mini Review

Abstract: Orthodontic treatments are concomitant with mechanical forces and thereby cause teeth movements. The applied forces are transmitted to the tooth root and the periodontal ligaments which is compressed on one side and tensed up on the other side. Indeed, strong forces can lead to tooth root resorption and the crown-to-tooth ratio is reduced with the potential for significant clinical impact. The cementum, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…Further studies by this group delved into the evaluation of the chemical composition of cementum [35] and the mechanical properties of pathologically altered cementum [36,37]. A review of the mechanical properties of the individual cells of cementum was made by Radermacher et al [38]. Hinrichs et al [39] found some new aspects of the microstructure of acellular cementum using scanning electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies by this group delved into the evaluation of the chemical composition of cementum [35] and the mechanical properties of pathologically altered cementum [36,37]. A review of the mechanical properties of the individual cells of cementum was made by Radermacher et al [38]. Hinrichs et al [39] found some new aspects of the microstructure of acellular cementum using scanning electron microscopy.…”
Section: Introductionmentioning
confidence: 99%